Asthma onset pattern and patient outcomes in a chronic rhinosinusitis population. Issue 4 (5th January 2018) - John Staniorski, Christopher; Price, Caroline P.E.; Weibman, Ava R.; Welch, Kevin C.; Conley, David B.; Shintani‐Smith, Stephanie; Stevens, Whitney W.; Peters, Anju T.; Grammer, Leslie; Lidder, Alcina K.; Schleimer, Robert P.; Kern, Robert C.; et al.
Abstract : Background: Chronic rhinosinusitis (CRS) is strongly associated with comorbid asthma. This study compares early‐onset and late‐onset asthma in a CRS population using patient‐reported and clinical characteristics. Methods: At enrollment into a clinical registry, CRS patients completed the 22‐item Sino‐Nasal Outcome Test (SNOT‐22), Asthma Control Test (ACT), mini‐Asthma Quality of Life Questionnaire (miniAQLQ), the 29‐item Patient‐Reported Outcomes Measurement Information System (PROMIS‐29), and medication use questionnaires. Patients also reported comorbid asthma and age at first asthma diagnosis. Early‐onset (<18 years) and late‐onset (>18 years) asthma groups were defined. Analysis of variance (ANOVA), chi‐square, and Kruskal‐Wallis tests were used to compare patient responses. Results: A total of 199 non‐asthmatic (56.1%), 71 early‐onset asthmatic (20.0%), and 85 late‐onset asthmatic (23.9%) CRS patients completed the survey. Body mass index (BMI) was significantly higher in late‐onset asthmatic ( p = 0.046) while age, gender, race, and smoking history did not differ with time of asthma onset. SNOT‐22, ACT, and miniAQLQ were not different between asthma groups, but late‐onset asthmatics had significantly lower physical function than non‐asthmatics ( p = 0.008). Compared to non‐asthmatics, late‐onset asthmatics showed increased rates of nasal polyps ( p < 0.001), higher Lund‐Mackay scores ( p = 0.005), and had received more oral steroid courses ( p < 0.001) and endoscopic surgeries ( p = 0.008) for CRS management. Late‐onset asthmatics compared to early‐onset asthmatics showed increased nasal polyposis ( p = 0.011) and oral steroid courses for CRS ( p = 0.003). Conclusion: While CRS‐specific and asthma‐specific patient‐reported outcome measures (PROMs) were not significantly different among groups, CRS patients with late‐onset asthma had poorer physical function, more frequent nasal polyposis, and required increased treatment for CRS. Late‐onset asthma may predict more severe disease in CRS.